Reproductive phenology of the non-woody community in a seasonally dry tropical forest and woodland in northeastern Brazil - Neves, Sâmia Paula Santos; de Araujo Fagundes, Adelly Cardoso; Bezerra-Silva, Alexsandro; dos Santos, Paulo Sérgio Neves; Rossatto, David Rodrigo [UNESP]; de Miranda, Lia d'Afonsêca Pedreira; Funch, Ligia Silveira (Elsevier, 2024)
Seasonally dry tropical forests and woodlands (SDTFW) represent one of the world's most endangered biomes. Approximately 56.3% of its species are non-woody, but little is known about their functional adaptations. The reproductive phenologies of 75 SDTFW species (supplementary material A 1) were studied according to their life forms and seed dispersal syndromes in northeastern Brazil. We used circular statistics and the GLM to assess their seasonalities and relationships of their phenologies with environmental variables. The community exhibited continuous pattern of flowering and fruiting. Flowering and fruiting by most species occurred during only a short period of time and were found to be related to rainfall and photoperiod. Moderate peaks in the seasonal activities of therophytes, hemicryptophytes, and camephytes were observed during the rainy season; succulents and epiphytes flowered all year around but fruited only seasonally. Dispersal modes exhibited seasonality of fruiting in the rainy season, with autochory being predominant over zoochory and anemochory. The observed overlapping of fruiting and flowering periods ensures a consistent resource supply throughout the year and contributes to the preservation of vital ecosystem services. These data highlight the importance of conserving these unique semiarid environments and also provide insights for conservation efforts aimed at preserving SDTFW and safeguarding their biodiversity.
Keywords: Caatinga; Dispersal modes; Dry lands; Life forms; Seasonality